Temporal patterns of physical activity in Olympic dinghy racing - Legg, S.; Mackie, H.; Smith, P. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: The objective of the present study was to determine the temporal patterns of physical activity in four classes of Olympic racing dinghy. METHODS: Experimental design: Descriptive. Setting: A field (on-water) study. Participants: Nineteen elite New Zealand sailors (fifteen male and four female). Intervention: Not applicable. Measures: The temporal pattern (duration and frequency) and nature of the physical activities of each sailor during each leg of simulated races were recorded on video tape and subsequently systematically quantified and categorised using notational analysis. The accumulated percentage of total leg time spent sitting (upright or leaning backwards), hiking (upright or fully extended) whilst trimming and whilst pumping the mainsheet and for the time spent on rig adjustments, tacking and gybing were calculated for both up-wind and off-wind sailing. RESULTS: When sailing up-wind, the most time was spent hiking upright (average 29-66% of total leg time) while trimming the mainsheet. During off-wind sailing, sailors spent the most time sitting upright while trimming the mainsheet (average 29-55% total leg time). Hiking upright while trimming the mainsheet was executed the greatest number of times (average 15.8-23.9) when sailing up-wind and sitting upright while trimming was executed the most times (average 3.5-7.4) when sailing off-wind. The most lengthy continuous activity was hiking upright while trimming the mainsheet when sailing up-wind (9-18 seconds) and sitting upright while trimming the mainsheet when sailing off-wind (17-34 seconds). CONCLUSIONS: The most physically demanding aspect of Olympic yacht racing is hiking. It occurs for the majority of up-wind legs when the wind starts to exceed approximately 8 knots. The only respite that the sailor gets from hiking is during tacking, rig adjustments or sitting in-board for brief periods when the wind is low. Sustained hiking tends to last for no more than approximately 20 seconds before the sailor changes to either a more extended or more upright hiking posture. The physical demands during off-wind sailing are generally less, except for a greater requirement for power in the arms and shoulders to pump the mainsheet in order to assist the dinghy in accelerating down waves. The findings of the present study are directly applicable to the design of sailing specific physical conditioning programmes for Olympic class sailors. http://www.minervamedica.it/journals2.t?f_Cat=R_180MSP